Concussions, cuts and cracked bones: A systematic literature review on protective headgear and head injury prevention in Olympic boxing - Tjønndal, A.; Haudenhuyse, R.; de Geus, B.; Buyse, L. (European Journal of Sport Science, 2022)
In 2013, the International Boxing Association (AIBA) prohibited the use of headguards for elite male Olympic boxing competitions. Could the removal of the headguard from elite male boxing competitions potentially cause increased injury risk for boxers? The aim of the literature review is to analyse current knowledge about the use of protective headgear and injury prevention in boxing, in order to determine if there are increased injury risks associated with headguard use. Peer-reviewed studies (language: English, Norwegian, Swedish, Danish and Dutch) published from 1980 and onwards were considered. Five academic databases and grey literature sources were searched, and articles were assessed for methodological quality. Only studies that included boxers as the study population with headguards as a factor were considered. A total of 39 articles were included in the review. The analysis of the reviewed literature indicates that headguards protect well against lacerations and skull fractures, while less is known about the protective effects against concussion and other traumatic brain injuries. Most of the analysed studies however use indirect evidence, obtained through self-report or observational techniques with relatively small non-representative samples. There are almost no randomised control trials, longitudinal research designs or samples from recreational boxing. Therefore, AIBA`s decision to remove the headguard has to be seen with caution and injury rates among (male) boxers should be continuously evaluated.